Millets have the potential to increase satiety and reduce the feeling of hunger: a systematic review - Anitha, Seetha; Upadhyay, Shweta; Kane-Potaka, Joanna (Frontiers in Sustainable Food Systems, 2024)
A systematic review was conducted to understand the satiety value of millets and their ability to lessen the feeling of hunger. Only six eligible studies had the relevant information for this analysis. These studies compared millet-based foods with refined rice, potatoes, wheat, oats, and rye, and found that millets have the potential to lower the hunger index. The proposed mechanism of this action suggests that this is due to the fact that millets are rich in fiber, which is responsible for increased gastric volume and increased gastric emptying time. Millet-based food stays longer in the stomach, thereby prolonging the feeling of satiety, or fullness. Fiber also helps to slow down the release of glucose into the blood. Furthermore, the protein content in millets increases insulin sensitivity, which too reduces the glucose response. This proposed mechanism of increasing satiety and delaying the glucose response is responsible for lowering the blood lipid profile and decreasing weight.